Pyruvate oxidation by the Reiter strain of Treponema phagedenis. - George, H A (American Society for Microbiology (ASM), 1982)
Spectrophotometric assays of pyruvate oxidation catalyzed by extracts of the Reiter strain of Treponema phagedenis indicated that viologen dyes, flavin nucleotides, and a ferric iron chelate, but not pyridine nucleotides, were utilized as electron acceptors. Benzyl viologen-linked activity partially sedimented during ultracentrifugation and appeared similar to clostridial pyruvate:ferredoxin oxidoreductase with respect to the spectral properties of the enzyme chromophore. Electron carrier activity in treponemal extracts was quantitated by a metronidazole-linked assay in which the oxidation of pyruvate by carrier-depleted extracts led to the reduction of electron carrier in the crude extracts which then reduced metronidazole. The rate of metronidazole reduction was proportional to the amount of electron carrier present in the assay. Electron carrier activity in Triton X-100-solubilized, crude extracts partially purified by DEAE-cellulose chromatography and gel filtration was attributed to a protein possessing the spectral and physical properties of a ferredoxin. A similar protein appeared to be present in extracts of Treponema denticola ST10.